Usage of a collagen elastin dermal matrix in the closure and reconstruction of a complex full-thickness plantar foot burn in a pediatric patient with Spina bifida: A case report - Jeffrey Litt; Mack Drake (Elsevier, 2024)
Background: Spina bifida cystica (SB) is one of the most common neural tube defects affecting 1 in 2,500 newborns worldwide. Due to the neurological deficits associated with SB, injuries from thermal exposure, trauma, or other etiology may be more severe rendering their treatment a challenge for a traditional approach to burn and wound management. Despite this relatively high disease incidence rate, few studies exist to evaluate wound development or the natural history of wound healing in patients with SB. Case presentation: We present a case of a pediatric patient with a history of SB who sustained a full thickness burn to the right plantar foot in February of 2023. The 8-year-old was riding an all-terrain vehicle when his right foot made contact with the hot tailpipe. The insensate neuropathy associated with the patient's SB contributed to the extreme severity of thermal contact injury. We report the burn, treatments, the usage of a novel dermal replacement, and outcomes of this case. Conclusion: This case demonstrates successful limb salvage in a pediatric patient with severe plantar foot burns utilizing a novel collagen-elastin dermal matrix for tissue reconstruction. Limb salvage was the preferred treatment option over amputation and a prosthetic considering the patient's age and need for future prostheses. Given the severity of the burn, the impaired wound healing due to his baseline neuropathy, and his baseline ambulatory status, the optimal outcome in this case was limb salvage, which was successfully achieved.